2003
DOI: 10.1023/a:1025703132523
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In human milk we previously found catalytic antibodies (abzymes) catalyzing hydrolysis of DNA, RNA, NMP, NDP, and NTP and also phosphorylation of proteins and lipids. In the present study we have analyzed nuclease activities of antibodies in blood of women during pregnancy and lactation. Blood of healthy male and female volunteers lacked catalytically active antibodies, whereas antibodies from blood of pregnant women hydrolyzed DNA and RNA and their relative activity varied over a wide range. Relative blood ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Taken together, in contrast to IgG from normal women before pregnancy and IgG from men, IgG from the serum of healthy pregnant women has DNAse and RNase activities which increase remarkably after the beginning of lactation [140], and this increase is much more significant in mothers who suffered from viral direases, for example, influenza or allergic diseases [140], or in females with induced AD during pregnancy [69]. Our data and the data in the literature show that the immune system of pregnant women may be stimulated by proteins and NAs in a different manner to that of normal humans.…”
Section: Fig 192mentioning
confidence: 86%
See 4 more Smart Citations
“…Taken together, in contrast to IgG from normal women before pregnancy and IgG from men, IgG from the serum of healthy pregnant women has DNAse and RNase activities which increase remarkably after the beginning of lactation [140], and this increase is much more significant in mothers who suffered from viral direases, for example, influenza or allergic diseases [140], or in females with induced AD during pregnancy [69]. Our data and the data in the literature show that the immune system of pregnant women may be stimulated by proteins and NAs in a different manner to that of normal humans.…”
Section: Fig 192mentioning
confidence: 86%
“…Therefore, we have compared the levels of DNase activity of IgG and IgM from the blood of pregnant healthy females without pathologies and women with an acute form of HT. It was shown that DNAse activity of Abzs in women with AD induced by pregnancy is overall about 4-5 times higher than this activity in the case of healthy pregnant women [140].…”
Section: Peculiarities Of the Immune Status Of Pregnant And Lactatingmentioning
confidence: 92%
See 3 more Smart Citations